2005
DOI: 10.1080/08037050510008814
|View full text |Cite
|
Sign up to set email alerts
|

Large artery stiffness and pulse wave reflection: Results of a population‐based study

Abstract: Of the studied arterial parameters, PAI showed the closest association with cardiovascular risk factors. The correlation between PAI and aortic PWV was loose, and both parameters had practically different determinants. PAI, which is obtained by direct measurement above radial artery, was practically identical with the mathematically derived CAI in the studied population sample, and therefore, it is a suitable parameter for studying the phenomenon of wave reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 16 publications
6
31
0
Order By: Relevance
“…24,[36][37][38][39][47][48][49][50][51][52][53]63 However, a few other studies did not consistently find this effect. 32,[40][41][42] For example, Filipovsky et al 41 and Rehill et al 42 found that AIx was significantly higher in smokers than in nonsmokers, while differences in PWV did not reach significance. Kool et al 32 also did not find significant differences between smokers and nonsmokers when measuring compliance and distensibility; however, they only included 14 nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,[36][37][38][39][47][48][49][50][51][52][53]63 However, a few other studies did not consistently find this effect. 32,[40][41][42] For example, Filipovsky et al 41 and Rehill et al 42 found that AIx was significantly higher in smokers than in nonsmokers, while differences in PWV did not reach significance. Kool et al 32 also did not find significant differences between smokers and nonsmokers when measuring compliance and distensibility; however, they only included 14 nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three different groups found no significant correlation between smoking status and increased cfPWV. [41][42][43] However, AIx was increased in smokers (17.25%) compared with nonsmokers (11.75%; P¼0.004) in one of the same subject Smoking and arterial stiffness RJ Doonan et al Smoking and arterial stiffness RJ Doonan et al populations. 42 A number of other studies found AIx to be increased in chronic smokers compared with nonsmokers.…”
Section: Chronic Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Arterial stiffness was assessed by pulse wave velocity (PWV), measured in supine position in the aorta, that is, between carotid and femoral arteries (aortic PWV, APWV) and in the lower extremity, that is, between femoral and dorsalis pedis or tibialis posterior arteries (peripheral PWV, PPWV). Consecutive registrations of the pulse waves are electrocardiogram gated and thus, the time shift between the appearance of wave at the first and the second sites can be calculated.…”
Section: Methodsmentioning
confidence: 99%
“…11 The first part of this examination was the registration of radial pulse wave which was used to evaluate wave reflection; the parameter showing wave reflection is augmentation index (AIx), defined as the ratio of pulse pressure at the peaks of secondary to primary wave. Immediately before the radial pulse wave registration, an additional BP reading was obtained using the Omron 705CP oscillometric device.…”
Section: Examinations and Materialsmentioning
confidence: 99%